2010
DOI: 10.1073/pnas.0912496107
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium vivax clinical malaria is commonly observed in Duffy-negative Malagasy people

Abstract: Malaria therapy, experimental, and epidemiological studies have shown that erythrocyte Duffy blood group-negative people, largely of African ancestry, are resistant to erythrocyte Plasmodium vivax infection. These findings established a paradigm that the Duffy antigen is required for P. vivax erythrocyte invasion. P. vivax is endemic in Madagascar, where admixture of Duffy-negative and Duffy-positive populations of diverse ethnic backgrounds has occurred over 2 millennia. There, we investigated susceptibility … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

22
354
2
3

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 349 publications
(390 citation statements)
references
References 46 publications
(42 reference statements)
22
354
2
3
Order By: Relevance
“…The low frequency of FY*A ES appears to be the result of its recent origin, which is reflected in its association with specific alleles at two microsatellite loci about 3 cM from FY (Zimmerman et al, 1999). Recently, Ménard et al (2010) also showed that there is about half as much expression in a sample from Madagascar for FY*A/FY*B ES heterozygotes as that for for normal homozygotes (FY*A/FY*A) or heterozygotes (FY*A/ FY*B). In other words, it does not appear that either the expression or the protection from ES alleles is recessive, but is intermediate between ES homozygotes and genotypes with two normal alleles.…”
Section: Duffymentioning
confidence: 99%
See 1 more Smart Citation
“…The low frequency of FY*A ES appears to be the result of its recent origin, which is reflected in its association with specific alleles at two microsatellite loci about 3 cM from FY (Zimmerman et al, 1999). Recently, Ménard et al (2010) also showed that there is about half as much expression in a sample from Madagascar for FY*A/FY*B ES heterozygotes as that for for normal homozygotes (FY*A/FY*A) or heterozygotes (FY*A/ FY*B). In other words, it does not appear that either the expression or the protection from ES alleles is recessive, but is intermediate between ES homozygotes and genotypes with two normal alleles.…”
Section: Duffymentioning
confidence: 99%
“…Perhaps the most definitive study is that of Ménard et al (2010) in Madagascar, a nation where endemic P. vivax is prevalent and a diverse ethnic population with both Duffynegative (FY*B ES /FY*B ES ) and Duffy-positive (having at least one allele that is FY*A or FY*B) individuals. In the sample examined of 476 asymptomatic Duffy-negative Population genetics of malaria resistance PW Hedrick individuals from eight locations, P. vivax was found in 8.8%.…”
Section: Duffymentioning
confidence: 99%
“…It has been proposed that due to the near-fixation of FY Ã O, P. vivax infection in humans is largely absent from equatorial Africa. An important recent discovery suggests low levels of P.vivax infection in FY Ã O homozygotes [13][14][15][16][17], which indicates that P. vivax might be evolving escape variants able to overcome the protective effect of FY Ã O. Phenotypic effects of the FY Ã A mutation are less clear than FY Ã O; however, there is evidence of natural selection and reduced P. vivax infection in individuals with this genotype ( [18,19], with conflicting reports in the Brazilian Amazon however [12,20,21]). …”
Section: Introductionmentioning
confidence: 99%
“…DBP-II is a three-subdomain (SD) protein, with SD2 contributing key residues for dimerization and receptor binding (19). Duffy-independent invasion has been reported for certain isolates of P. vivax (29); however, these isolates contain a gene duplication of DBP, suggesting that increased expression of DBP may facilitate Duffy-negative invasion (30).…”
mentioning
confidence: 99%